Pembelajaran Pendidikan Jasmani Sekolah Dasar di DKI Jakarta - Taufik Yudi Mulyanto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The purpose of the study was to obtain information among teachers of Physical Education (PE) in Special Capital District of Jakarta concerning their teaching practice. The sample, 79 in number, was taken from a population of teachers of PE in elementary schools, graduating from senior high schools and from PE program of SGO, DIII, and S1. The results reveal that the teaching practice emphasized the development of children’s physical aspect (48.27%), followed by cognitive and affective aspects. Teaching materials were suited to child development and teaching activities included planning, teaching (warming-up, exercise, core exercise, and closing or cooling down), and evaluating.